(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Regarded as the Father of First Aid and surgical haemostasis for the war wounded soldiers, Johann Friedrich August von Esmarch was one of the greatest military surgeons ever born. His contributions range from devising his own illustrated bandage to application of tourniquet to prevent blood loss in trauma victims in the battlefield. He has also invented an inhalation mask for chloroform anesthesia, splints and surgical instruments. He changed the way the war wounds were managed and made many serious war injured victims go home alive J Bangladesh Coll Phys Surg 2023; 41: 244-247